Chickpea Genotypes Contrasting for Vigor and Canopy Conductance Also Differ in Their Dependence on Different Water Transport Pathways - Sivasakthi, Kaliamoorthy; Tharanya, Murugesan; Kholová, Jana; Wangari Muriuki, Ruth; Thirunalasundari, Thiyagarajan; Vadez, Vincent (Frontiers in Plant Science, 2017)
Lower plant transpiration rate (TR) under high vapor pressure deficit (VPD) conditions and early plant vigor are proposed as major traits influencing the rate of crop water use and possibly the fitness of chickpea lines to specific terminal drought conditions—this being the major constraint limiting chickpea productivity. The physiological mechanisms underlying difference in TR under high VPD and vigor are still unresolved, and so is the link between vigor and TR. Lower TR is hypothesized to relate to hydraulic conductance differences. Experiments were conducted in both soil (Vertisol) and hydroponic culture. The assessment of the TR response to increasing VPD showed that high vigor genotypes had TR restriction under high VPD, and this was confirmed in the early vigor parent and progeny genotype (ICC 4958 and RIL 211) having lower TR than the late vigor parent and progeny genotype (ICC 1882 and RIL 022). Inhibition of water transport pathways [apoplast and symplast (aquaporins)] in intact plants led to a lower transpiration inhibition in the early vigor/low TR genotypes than in the late vigor/high TR genotypes. De-rooted shoot treatment with an aquaporin inhibitor led to a lower transpiration inhibition in the early vigor/low TR genotypes than in the late vigor/high TR genotypes. Early vigor genotypes had lower root hydraulic conductivity than late vigor/high TR genotypes. Under inhibited conditions (apoplast, symplast), root hydraulic conductivity was reduced more in the late vigor/high TR genotypes than in the early vigor/low TR genotypes. We interpret that early vigor/low TR genotypes have a lower involvement of aquaporins in water transport pathways and may also have a smaller apoplastic pathway than high TR genotypes, which could explain the transpiration restriction under high VPD and would be helpful to conserve soil water under high evaporative demand. These findings open an opportunity for breeding to tailor genotypes with different “dosage” of these traits toward adaptation to varying drought-prone environments.